Does a therapist's reflective ability predict the accuracy of their self-evaluation of competence in cognitive behavioural therapy?. (30th March 2016) - Loades, Maria E.; Myles, Pamela J.
Abstract: Accurately evaluating how competently one is performing can be a precursor to seeking training and supervision, therefore contributing to safe, effective practice. Little is known about what predicts accurate self-evaluation. Prior research findings are inconsistent, with overestimation of self-rated competence in some studies and underestimation in others. We aimed t o explore the relationship between therapists' reflective ability and the level of agreement between self-rated competence and competence rated by an experienced CBT assessor. Thirteen trainees undertaking a postgraduate CBT diploma submitted a series of recordings accompanied by self-ratings using the Cognitive Therapy Scale – Revised (CTS-R) and related written reflective analyses. Independent assessors marked the written analyses using a standardized marking scheme and rated the therapy sessions using the CTS-R. Trainees tended to overestimate or underestimate their competence in comparison to the independent assessors. The level of agreement between the assessors' ratings and self-evaluation of competence tended to improve during training, while reflective ability did not. Reflective ability was significantly related to level of agreement between self-rated and assessor-rated competence. Trainees do not consistently demonstrate the bias for overestimating their competence previously found in qualified therapists. During training, the tendency of an individual to over- or underestimate their competence may not remain stable, but tends to become more consistent with ratings undertaken by an experienced CBT assessor. Trainees who were rated as more reflective, tended to agree more closely with independent assessors on evaluation of competence. Therefore, enhancing reflective ability may help therapists to more accurately self-evaluate their competence.